Recent Insights in Petroleum Science and Engineering 2018
DOI: 10.5772/intechopen.70108
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Crude Oils and the Precipitated Asphaltenes Fraction using UV Spectroscopy, Dynamic Light Scattering and Microscopy

Abstract: Analysis of crude oil composition provides important information that impacts on the recovery, handling, and transportation of hydrocarbons. Crude characterization also provides data in the analysis of geochemistry of the source of origin. Crude oil characterization by optical methods is usually diicult because of its dark color; however, those characterizations are crucial because they give information that can afect some analysis procedures. Ultraviolet-visible (UV-vis) spectroscopy is a simple and practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Furthermore, the absorption coefficients of asphaltenes exhibited variability across their diverse molecular compositions. Banda-Cruz et al identified the UV signals of benzenic, naphthenic, and Soret compounds, which correspond to petroleum porphyrins in crude oil and extracted asphaltenes. Derivative UV–vis spectroscopy was employed to validate the existence of an archipelago-type architecture within the asphaltene mixture, and the absorption spectrum identified benzenic compounds, naphthenic compounds, aromatic chromophores, and vanadium petroleum porphyrins .…”
Section: Chemical Structures Of Asphaltenesmentioning
confidence: 99%
“…Furthermore, the absorption coefficients of asphaltenes exhibited variability across their diverse molecular compositions. Banda-Cruz et al identified the UV signals of benzenic, naphthenic, and Soret compounds, which correspond to petroleum porphyrins in crude oil and extracted asphaltenes. Derivative UV–vis spectroscopy was employed to validate the existence of an archipelago-type architecture within the asphaltene mixture, and the absorption spectrum identified benzenic compounds, naphthenic compounds, aromatic chromophores, and vanadium petroleum porphyrins .…”
Section: Chemical Structures Of Asphaltenesmentioning
confidence: 99%
“…p à electronic transitions in conjugated aromatic structures [72]. The exponential decay profile is due to the intense light scattering in wavelength less than 400 nm caused by asphaltene macromolecules present in the sample [73]. In addition, a possible explanation for the slight increase in the fraction of light absorbed after 40 h of irradiation involves a process of evaporation of the compounds with lower boiling points.…”
Section: Photodegradation Of Petroleum Over Time By Synchronous Fluor...mentioning
confidence: 99%
“…It is found to be sensitive to many variables, such as the source of asphaltenes, quality of the solvent, and properties of the adsorbent. Researchers have employed a variety of experimental techniques to characterize asphaltene adsorption such as contact angle measurements, AFM, , NIR/UV–vis spectroscopy, quartz crystal microbalance (QCM) gravimetry, , ellipsometry, and electrokinetic measurements. , The source of asphaltenes determines the chemical functionalities of the asphaltene molecules, which impact the extent of asphaltene adsorption on the same adsorbents. Two studies, conducted by Pernyeszi and Marczerski, may be used to highlight how these geographic differences result in different adsorption behavior onto various clay minerals. , Both researchers studied the static adsorption of asphaltenes dissolved in toluene onto different clay minerals, such as kaolinite, illite, and montmorillonite, using UV–vis spectroscopy.…”
Section: Introductionmentioning
confidence: 99%